Strategic Planning Approach to the Development of Contract Farming in the Egyptian Sugar Industry - Hazem S. Kassem; Bader Alhafi Alotaibi; Salim Bagadeem (Journal of Agricultural Extension, 2020)
Contract farming is an inclusive business model for ensuring sustainability and profitability in the agricultural sector. The strategies required to develop contract farming in the Egyptian sugar industry were examined by applying the Strength-Weakness-Opportunities-Threats (SWOT) approach in combination with an analytic hierarchy process. The data were collected from sugar beet farmers, extension workers, experts, and employees of the Dakhalia Sugar and Refining Company in Egypt. The results reveal that reduced market risk has the highest overall priority score among the strengths. Non-commitment of farmers to harvest time received the highest overall priority score among the weaknesses, while valorization of sugar industry wastes had the highest overall priority score among the opportunities, and accumulation of large reserves of sugar at the factory was perceived as the most important threat to the sugar industry. These findings can be used to formulate strategies based on current situation analysis and create suitable conditions for successful contract farming in the sugar sector.